AN ANALYSIS OF ABSTRACT USING MOVE MODEL ON HYLAND’S THEORY IN PROJECT JOURNAL ARTICLE - Mu'man Mu'man (ETERNAL (English Teaching Journal), 2022)
An abstract is one of the important parts in a research paper. It must give detail information to the readers. This research aimed to analyze abstracts’ content by using Move model proposed by Hyland (2003). It consists of introduction, purpose, method, result or product, and conclusion.  This research used a qualitative method which specifically used content analysis design. Content analysis design was used because the researcher analyzed the content of abstracts taken from PROJECT Journal article which meant whether the writers presented the detail information as Move model or not. Evidently, from 15 articles analyzed, it was only one person who displayed detail information which was appropriate with Move model and the others were still not what the researcher expected except in informing the methods used. From the result of analysis, the understanding of writers about giving detail information in an abstract still lacks. It proves that the data finding presented in the result showed the weakness of abstracts which were not suitable yet with Move model.